(untitled) (Scientific journal of the Fergana State University, 2025)
This study examines the mechanisms of implementing state policy for mitigating emergency environmental situations and explores international experience in this field. The research analyzes the experience of developed countries such as Germany, the USA, Japan, and South Korea, and assesses the possibilities of adapting their practices to Uzbekistan’s context. The study proposes measures for improving legal, economic, and technological mechanisms. Recommendations are provided on integrating foreign models into Uzbekistan’s environmental risk management system.